Method for preparing monodisperse single crystal cathode material

By using a combination of metal salt solution and alkaline solution to form a metal hydroxide precursor when preparing a single crystal cathode active material, and heating it in one-step calcination, the problems of particle size control and complex process in the prior art are solved, and the process is simplified and high-quality monodisperse single crystal material is obtained.

CN119816475APending Publication Date: 2025-04-11REDWOOD MATERIALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063224.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-08
Filing Date
2023-09-05
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to control the particle size when preparing single crystal cathode active materials, and often requires multiple calcination or annealing steps, which is complicated in the process.

Method used

By providing a combination of a metal salt solution containing nickel, cobalt, manganese, aluminum or a combination thereof and an alkaline solution, the pH value is controlled to be no more than 10 to form a metal hydroxide precursor, and heating in one step of calcination to form a monodispersed single crystal cathode active material.

Benefits of technology

A simplified process is implemented, multiple calcination or annealing steps are avoided, and a monodispersed single crystal cathode active material with a single peak particle size distribution and a desired particle size distribution is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816475A_ABST
    Figure CN119816475A_ABST
Patent Text Reader

Abstract

A method comprising: providing a metal salt solution comprising nickel, cobalt, manganese, aluminum, or a combination thereof; the metal salt solution is combined with an alkaline solution, where the combination of the metal salt solution and the alkaline solution is maintained at a pH of not greater than 10 to form a metal hydroxide precursor. To form the cathode active material, the method further includes adding a lithium compound to the metal hydroxide precursor to form a metal hydroxide precursor mixture; and heat treating the metal hydroxide precursor mixture to form the single crystal cathode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Citations of Related Applications

[0002] This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 404,579, filed on September 8, 2022, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] The field of the invention is methods of preparing single-crystalline cathode active materials. Background Art

[0004] Single crystal cathode active materials (CAMs) for lithium-ion batteries can have advantages over conventional layered oxide cathode active materials. For example, single crystal cathode active materials (sometimes referred to as monolithic cathode active materials) can have one or more of high mechanical strength, structural stability, thermal stability, and long cycle life compared to polycrystalline secondary agglomerated cathode active materials.

[0005] Previous attempts to prepare single crystal CAMs have included co-precipitation followed by multiple calcination or annealing steps. See, for example, WO2020 / 082019. Particle size control can be challenging. Therefore, co-precipitation methods can sometimes involve grinding the initial calcined particles, followed by one or more further annealing steps. See, for example, WO2022 / 026014. Other methods include the use of molten salts, sol-gel processing, and hydrothermal reactions.

[0006] A simplified method for providing monodisperse single crystalline particles having a desired particle size would be an advance in the art. Summary of the invention

[0007] Disclosed herein is a method for preparing a single crystalline cathode active material, the method comprising: providing a metal salt solution comprising nickel, cobalt, manganese, aluminum, or a combination thereof; combining the metal salt solution with an alkaline solution, wherein the combination of the metal salt solution and the alkaline solution is maintained at a pH of no greater than 10 to form a metal hydroxide precursor; adding a lithium compound to the metal hydroxide precursor to form a metal hydroxide precursor mixture; and heat treating the metal hydroxide precursor mixture to form a single crystalline cathode active material.

[0008] Also disclosed herein is a method for preparing a monodisperse single crystal cathode active material, the method comprising: providing a metal hydroxide precursor comprising nickel, cobalt, manganese, aluminum, or a combination thereof, wherein the metal hydroxide precursor is characterized by being semi-crystalline and comprising a β phase and an intermediate phase, wherein the β phase is characterized by that when Cu K αWhen analyzed by X-ray diffraction, the peak at 17 to 23 degrees 2θ of the radiation, the mesophase is characterized by incorporating H2O, ROH, RCOOH, anions, or a combination thereof into the structure of the mesophase, where R is an alkyl group having 1 to 3 carbon atoms; adding a lithium compound to a metal hydroxide precursor to form a mixture; and heating the mixture in a one-step calcination to form a monodisperse single-crystal cathode active material, the monodisperse single-crystal cathode active material having a single-peak particle size distribution and a D50 particle size distribution of 100 nanometers (nm) to 5 micrometers (μm) or a D90 particle size distribution of 1 to 10 μm.

[0009] In addition, a metal hydroxide composition is disclosed herein, which comprises: a metal hydroxide, the metal hydroxide comprising nickel, cobalt, manganese, aluminum, or a combination thereof, where the metal hydroxide is characterized as semi-crystalline and comprises a β-phase and a mesophase, the β-phase being characterized by, when analyzed by X-ray diffraction using Cu K α the peak at 17 to 23 degrees 2θ of the radiation, and having the formula M(OH)2, where M is Ni, Co, Mn, Al, or a combination thereof, the mesophase being characterized by incorporating H2O, ROH, RCOOH, anions, or a combination thereof into the structure of the mesophase, where R is an alkyl group having 1 to 3 carbon atoms.

[0010] A single-crystal cathode active material is also disclosed, having the formula Li x MO2, where M is Ni, Co, Mn, Al, or a combination thereof, and 0 < x ≤ 1.2, and being characterized by a single-peak particle size distribution and a D50 particle size distribution of 100 nm to 5 μm, or a D90 particle size distribution of 1 to 10 μm, and the presence of Li2SO4. Description of the Drawings

[0011] Now referring to the drawings, which are exemplary embodiments, and wherein like element numbers are the same.

[0012] Figure 1 is a scanning electron micrograph (SEM) of the co-precipitated particles according to Example 1.

[0013] Figure 2 is the SEM of the co-precipitated particles according to Example 2.

[0014] Figure 3 is the SEM of the co-precipitated particles according to Example 3.

[0015] Figure 4 is the SEM of the co-precipitated particles according to Example 4.

[0016] Figure 5 is a SEM of the co-precipitated particles according to Example 5.

[0017] Fig. 6A is a SEM of cathode active material particles according to Example 6.

[0018] Figure 6B is a SEM of cathode active material particles according to Example 6.

[0019] Figure 7 is a graph of intensity (arbitrary units) versus diffraction angle (degrees 2θ) showing the results of X-ray diffraction (XRD) analysis for the mixed metal hydroxides of Comparative Example 1 and Examples 1-4 when analyzed using Cu Ka radiation.

[0020] Figure 8 is a graph of intensity (arbitrary units) versus diffraction angle (degrees 2θ) showing X-ray diffraction (XRD) analysis for the mixed metal hydroxide of Example 5 when analyzed using Cu Ka radiation.

[0021] Fig. 9 is a graph of intensity (arbitrary units) versus diffraction angle (degrees 2θ) showing the results of X-ray diffraction analysis for the cathode active material of Example 6 when analyzed using Cu Ka radiation.

[0022] Fig.10 is a graph of intensity (arbitrary units) versus diffraction angle (degrees 2θ) showing X-ray diffraction analysis for the cathode active material of Example 7 when analyzed using Cu Ka radiation.

[0023] Fig.11 is a graph of distribution density versus particle size (micrometers, μm), showing the particle size distribution for the cathode active material particles synthesized in Example 6.

[0024] Fig.12 is a graph of distribution density versus particle size (micrometers, μm), showing the particle size distribution for the cathode active material particles synthesized in Comparative Example 2.

[0025] Fig.13 is a graph of intensity (arbitrary units) versus diffraction angle (degrees 2θ) showing the results of X-ray diffraction analysis for the cathode active material of Comparative Example 2 when analyzed using Cu Kα radiation. DETAILED DESCRIPTION

[0026] The methods disclosed herein provide an effective means for preparing monodisperse single crystal cathode active materials without the multiple calcination or annealing steps, grinding, complex chemistry, or high energy processes typically associated with sol-gel, molten salt, or hydrothermal methods.

[0027] In particular, it has been found that careful control of pH during the coprecipitation of metal sulfate solutions can produce unique metal hydroxide precursors. It has further been found that such unique metal hydroxide precursors can be mixed with lithium compounds and readily calcined into monodisperse single crystal cathode active material particles having small particle sizes. The calcination can be carried out in a single step, although additional steps are not excluded.

[0028] Metal hydroxide

[0029] The metal hydroxide precursors formed or used in the methods disclosed herein can be characterized as including a β-phase and an intermediate phase. The β-phase can be characterized in that, when analyzed using Cu Kα radiation, X-ray diffraction (XRD) shows peaks in the 2θ range of 17 to 23 degrees. The β-phase can be crystalline, amorphous, or a combination comprising crystalline particles and amorphous particles. The β-phase can have the formula M(OH)2, where M is a metal. For example, the metal M can be nickel, cobalt, manganese, aluminum, or a combination thereof. As another example, the metal can comprise nickel, cobalt, and manganese in a molar ratio of greater than 0 to 1 mole of nickel: greater than 0 to 1 mole of cobalt: greater than 0 to 1 mole of manganese or preferably 1 mole of nickel: 0.1 to 0.2 moles of cobalt: 0.1 to 0.2 moles of manganese. For example, the molar ratio of nickel: cobalt: manganese can be 1:0.125:0.125 or 1:0.18:0.18.

[0030] In some cases, the X-ray diffraction pattern can also or alternatively show an α-phase. The α-phase is characterized by peaks in the 2θ range of 5 to 15 degrees when analyzed by X-ray diffraction using Cu K α radiation. Commercially available X-ray diffractometers (such as, for example, Rigaku TM Miniflex) can be used to measure the X-ray diffraction.

[0031] The intermediate phase can be characterized by peaks or an upward slope in the XRD pattern in the 2θ range of 15 to 17 degrees when analyzed by X-ray diffraction using Cu K α radiation, or characterized in that it includes water, solvent, or anions present in the structure of the intermediate phase. The intermediate phase can have the formula M(OH)2·yZ, where 0 < y < 0.75 and Z represents H2O, solvent, anion, or a combination thereof. For example, as the solvent, Z can be ROH or RCOOH, where R is an alkyl group having 1 to 3 carbon atoms. As the anion, Z can be, for example, OH- , SO4 2- , NO3 - , CO3 2- , F - , Cl - , or a combination thereof. Z is preferably water or sulfate ion, and more preferably water. The Z element is incorporated into the structure of the mesophase. In one aspect, 0 < y < 0.75, 0.1 < y < 0.65, or 0.2 < y < 0.55.

[0032] Based on the total weight of the metal hydroxide precursor, the metal hydroxide precursor may contain residual sulfur in an amount of at least 0.1 weight percent (wt%) to less than 3 wt%, preferably less than 2.5 wt%, more preferably less than 2 wt%.

[0033] In one aspect, the metal hydroxide precursor has a tapped density of 0.1 grams per cubic centimeter (g / cc) to 1.5 g / cc, preferably 0.1 to 1 g / cc, more preferably 0.1 to 0.5 g / cc. The tapped density can be determined according to ASTM B527, the content of which is incorporated herein by reference in its entirety.

[0034] Method for preparing metal hydroxide

[0035] To prepare the metal hydroxide precursor, a metal salt solution can be provided. Combining the metal salt solution with an alkaline solution can cause precipitation of the metal hydroxide precursor. The metal salt solution contains a metal salt of nickel, cobalt, manganese, aluminum, or a combination thereof.

[0036] For example, the metal salt solution can be a metal sulfate solution, a metal hydroxide solution, or a metal nitrate solution. The metal salt solution can contain one metal or a mixture of two or more metals. In the solution, the metal will exist in ionic form. In one aspect, the metal salt solution is an aqueous solution of sulfate. The sulfate can include nickel sulfate, manganese sulfate, cobalt sulfate, aluminum sulfate, or a combination thereof. The use of NiSO4·6H2O-, MnSO4·H2O, and CoSO4·7H2O is mentioned.

[0037] The concentration of the metal salt in the metal salt solution can be, for example, 0.2 to 2.2 moles of metal salt per kilogram of solvent (molal, m), or 0.2 to 3 moles of metal salt per liter of solution (molar, M). The solvent in the metal salt solution can contain water. The metal salt solution can contain metal obtained from recycled raw materials, preferably metal obtained from post-industrial recycled raw materials, post-consumer recycled raw materials, or a combination thereof. In one aspect, nickel, cobalt, manganese, aluminum, or a combination thereof in the metal salt solution is obtained from recycled raw materials.

[0038] The alkaline solution may include an alkali metal hydroxide, ammonium hydroxide, or a combination thereof. Any suitable alkali metal hydroxide may be used. The alkali metal may be Li, Na, K, Rb, Cs, Fr, or a combination thereof. For example, the alkali metal hydroxide and ammonium hydroxide may be present in a molar ratio of 2:1 to 1:2, or 1.5:1 to 1:1.5, or 1.2:1 to 1:1. If the alkaline solution includes a combination, a separate solution may be added to the metal salt solution, or the alkaline solution may be pre-combined and then combined with the metal salt solution. The concentration of ammonia may be 0.2 to 20 molar concentrations, or 0.2 to 19 mass molar concentrations. The concentration of the alkali metal hydroxide may be 0.2 to 20 mass molar concentrations, or 0.2 to 30 mass molar concentrations.

[0039] The alkaline solution and the metal salt solution can be combined in a batch mode. Alternatively, one of the metal salt solution and the alkaline solution can be provided in a container and the other solution can be added as a continuous feed. As another example, both the alkaline solution and the metal salt solution can be added continuously to the container.

[0040] The pH of the combination of the metal salt solution and the alkaline solution is no greater than 10, preferably less than 10. At greater pHs, no alpha phase or mesophase is observed by X-ray diffraction. At a pH of 7 to 8, the alpha phase is observed and mesophase and beta phase may not be observed. At a pH of at least 8 up to 10, a useful combination of beta phase and mesophase is observed. Thus, the pH of the combination of the metal salt solution and the alkaline solution can be at least 8, or at least 8.5, or at least 9, or at least 9.5, or at most 10, or at most 9.5, or at most 9, or at most 8.5.

[0041] The combination can be heat treated at a temperature in the range of 25 to 60 ° C. The combination can be stirred, for example, in a continuously stirred tank reactor. The stirring rate can be in the range of 200 to 1000 RPM. The metal hydroxide formed in the combined solution can have a solid loading (solid loading, solid loading) of 2 to 20wt%, preferably 5 to 15wt%, more preferably 8 to 15wt% based on the gross weight of the combined solution. The precipitate of the metal hydroxide can be collected by any suitable solid-liquid separation technique, for example, by filtering, centrifuging, decanting or other suitable solid / liquid separation methods or their combination. The separated precipitate can be washed. The filtrate conductivity can be reduced to a desired level by washing, for example, reduced to less than 400 micro-Siemens / cm (μS / cm) or less than 350μS / cm.

[0042] Method for preparing monodisperse single crystal cathode active material

[0043] As discussed above, the metal hydroxides can be used to form a cathode active material. In particular, a lithium compound can be added to the metal hydroxide to form a mixture, which is then heated to form the cathode active material.

[0044] Surprisingly, it has been found that when the metal hydroxide contains a β-phase and an intermediate phase, small, single-peak, monodisperse single-crystalline cathode active materials can be formed in a single heating step. Without wishing to be bound by theory, it is possible that the β-phase acts as a nucleus and the intermediate phase acts as a particle growth reagent that promotes particle growth during heating (e.g., calcination).

[0045] The lithium compound can include lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or a combination thereof. The molar ratio of the lithium compound to the metal hydroxide compound can be from 1 to 1.2, preferably from 1.02 to 1.15, or more preferably from 1.05 to 1.10.

[0046] The heating step can include calcination or sintering and can include heating at a temperature of from 600 to 1100 °C, preferably from 800 to 1000 °C, and more preferably from 850 to 950 °C. The heating can occur, for example, for 2 to 24 hours. Although it has been found that a single heating step forms small, single-peak, monodisperse single-crystalline cathode active materials, additional heating steps can be used. In some cases, based on the total weight of the mixture, the mixture subjected to heating can contain from 0.1 to 4 wt% of lithium carbonate. In some aspects, the method excludes additional heating steps.

[0047] The method can further include washing the cathode active material after heating. The washing can include washing with any suitable liquid, such as water, or an aqueous solution of water and C 1-4 alcohol (e.g., methanol, ethanol, isopropanol, butanol). Washing with water is mentioned.

[0048] Monodisperse single-crystalline cathode active material

[0049] The monodisperse single-crystalline cathode active material formed by the above method can have the formula Li x MO2, where M is Ni, Co, Mn, Al, or a combination thereof, and 0 < x ≤ 1.2. For example, the single-crystalline cathode active material can have the formula Li x Ni y Co z Mn vO2, where 0 < x ≤ 1.2 and 0.8 ≤ (y + z + v) ≤ 1.1. In one instance, y can be from 0.1 to 1, z can be from 0.01 to 0.1, and v can be from 0.01 to 0.1. Preferably, y can be from 0.5 to 1, z can be from 0.02 to 0.1, and v can be from 0.02 to 0.1. As a specific instance, y can be from 0.7 to 1, z can be from 0.02 to 0.1, and v can be from 0.02 to 0.1. In one aspect, the single-crystal cathode active material can have the formula LiNi 0.88 Co 0.06 Mn 0.06 O2.

[0050] The single-crystal cathode active material can have a unimodal particle size distribution, be monodisperse, and have a small particle size. For example, the D50 particle size can be at least 100 nanometers (nm) to less than 20 micrometers (μm). Within this range, the D50 particle size can be 500 nm to 10 μm, or 1 to 5 μm, or 1 to 3 μm. The D90 particle size can be 1 to 20 μm. Within this range, the D90 particle size can be 3 to 20 μm, or 5 to 8 μm. A particle size analyzer such as the HELOS-RODOS model H3365 can be used to determine the particle size and distribution. The wet method can be used to determine the particle size. The D50 particle size represents the median diameter, i.e., the particle size at 50% in the cumulative distribution. The D90 particle size represents the particle size at the 90% cumulative distribution, meaning that 90% of the particles are smaller than this particle size. The D50 particle size, D90 particle size, and particle size distribution can be determined according to ASTM C115, the content of which is incorporated herein by reference in its entirety.

[0051] The single-crystal active material made using sulfate according to the method disclosed herein can have residual Li2SO4. When analyzed using Cu K α radiation, the presence of sulfate can be determined by an X-ray diffraction peak at 22 to 29 degrees 2θ, as Fig. 9 shown.

[0052] Based on the total weight of the cathode active material, on the surface of the cathode active material, the cathode active material contains less than 10 wt%, or less than 7 wt% of residual lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium sulfate, or a combination thereof. For example, based on the total weight of the cathode active material respectively, on the surface of the cathode active material, the cathode active material can contain from 0 to 10 wt%, or from 0 to 7 wt%, or from 0 to 5 wt%, or from 0 to 3 wt%, or greater than 0 to 10 wt%, or greater than 0 to 7 wt%, or greater than 0 to 5 wt%, or greater than 0 to 3 wt% of residual lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium sulfate, or a combination thereof.

[0053] In one aspect, the cathode active material is characterized by an average discharge capacity of greater than 200 milliamp-hours per gram (mAh / g) for a half-cell over 100 cycles at a discharge rate of C / 3. The half-cell may use a lithium metal anode. The C / 3 rate refers to the current that discharges the cell in 3 hours and may be determined using a cathode active material specific capacity of 230 mAh / g.

[0054] Methods of forming electrodes and batteries

[0055] The cathode active materials disclosed herein can be used to form a cathode by combining the cathode active material with a conductive material such as carbon black and a binder material such as a suitable polymer material (e.g., polyvinylidene fluoride, a cellulose polymer, etc.), and applying the combination to a current collector. The combination can be in the form of a slurry with a carrier solvent such as N-methylpyrrolidone (NMP). The electrode can be used in an energy storage device.

[0056] Example

[0057] Test method:

[0058] In the examples, the particle size distribution (PSD) was characterized using a HELOS & RODOS model H3365 (software PAQXOS 5.1.1) particle size analyzer. For analysis, less than 100 milligrams (mg) of powder was dispersed in 20 milliliters (mL) of water by 1 minute of ultrasonic treatment prior to analysis. The measurements were performed using a standard measuring range (e.g., R3 and R5: 0.5 to 875 μm). In the examples, a Rigaku TM Miniflex was used for X-ray diffraction (XRD) analysis. A Cu radiation source with a voltage of 40 kV and 15 mA was used. The wavelengths for Ka1 and Ka2 were and Scanning conditions: 1D scanning (θ / 2θ, D / tex Ultra detector) was performed with a step width of 0.01° and a scan rate of 10° / min. The scanning range was 5 to 80 degrees 2θ.

[0059] Using Phenon TM Scanning electron micrographs were collected using an XL microscope. The accelerating voltage was 15 kV and the magnification was 20,000-25,000x. Backscattering mode was used for all images.

[0060] By Metrohm TMThe residual Li quantification was characterized by automated titration to measure the residual lithium content in the cathode active material. The titration was performed using a HCl (0.1 normal (N)) standard and two titration endpoints were detected. The two endpoint pH values ​​corresponded to 8.1 and 4.4, respectively. The lithium hydroxide and lithium carbonate content (wt%) can be determined by the volume of HCl required to reach the first and second titration endpoints.

[0061] Electrode preparation: Cathode active material (CAM) powder was mixed with conductive carbon black and PVDF binder in a ratio of 94:3:3 by weight. N-methyl-2-pyrrolidone (NMP) was used to adjust the slurry rheology. The mixture was precipitated with THINKYMIXER TM Planetary mixer mixing. Mixing conditions: repeat 2000RPM, last 1 minute, mix ten times, there is a 1 minute rest period between mixing. The slurry is then cast on Al foil using a 254mm scraper, followed by drying at 60°C to remove most of the NMP solvent, and then drying at 120°C for 5 minutes. The cast film is then further dried overnight at 110°C under vacuum for at least 12 hours to ensure proper drying and PVDF curing. A button half-cell (CR2032) with a Li metal anode is assembled using an electrolyte including 1.2M LiPF6 in ethylene carbonate (EC): ethyl methyl carbonate (EMC) (3:7v / v%) + 2wt% vinylene carbonate (VC), and tested using an Arbin tester.

[0062] Electrochemical testing protocol: The button half-cells were first charged using a constant current / constant voltage (CC-CV) protocol with a C / 10 constant charge current until a cut-off voltage of 4.3 V, followed by a constant voltage charge until the charge current dropped to C / 20. The cells were then discharged at different C rates with a discharge cut-off voltage of 2.8 V. The charge and discharge rates were determined based on the weight of the cathode active material and an assumed specific capacity of 230 mAh / g.

[0063] Comparative Example 1

[0064] A metal sulfate solution (MSO4) of NiSO4·6H2O, MnSO4·H2O, and CoSO4·7H2O in water and having a total concentration of 2 moles per liter (M) was prepared, wherein the stoichiometric ratio of Ni:Mn:Co was 8:1:1. Separate feeds of aqueous ammonium hydroxide (NH4OH) solution (5M) and NaOH solution (2M) were used as chelating agent and precipitant, respectively. A 3 liter (L) continuous stirred tank reactor (CSTR) was charged with 0.75M NH4OH solution, followed by addition of the metal sulfate solution (MSO4), NH4OH, and NaOH together. The flow rates of the MSO4 and NH4OH feeds were maintained at 0.108 liters / hour (L / h) and 0.083 L / h, respectively, thereby maintaining the molar ratio of NH3:M constant at 1.92. The NaOH addition rate was also maintained constant at 0.108 L / h to facilitate continuous precipitation. After 48-50 hours the system reached a steady state where all reagent concentrations were constant. The reactor temperature was maintained at 50°C using a stirring rate of 1085 revolutions per minute (RPM). The solution pH was maintained constant at 11.3 by adjusting the metal and NH4OH feeds. The solution was continuously purged with N2 and covered with N2 to prevent oxidation of the transition metal. The X-ray diffraction (XRD) pattern of the product is shown in Figure 7 middle.

[0065] Example 1

[0066] A 0.6 m (molar mass concentration, i.e., moles of solute (e.g., mixed metal sulfate) / kg of solvent) mixed metal sulfate solution (Ni / Co=90 / 10) and an alkaline solution (i.e., 0.6 m aqueous NH4OH solution (aq), prepared using deionized (DI) water) were prepared. The mixed metal solution and the alkaline solution were preheated to 40°C. Equal amounts of the mixed metal and alkaline solutions (i.e., 100 milliliters (mL) of each) were premixed in a 1 liter (L) reaction vessel and maintained at 40°C. The mixed metal solution and the alkaline solution were added together to the reactor at a rate of 1 mL / min, and mixing was continued for 5 hours. The pH of the solution was 7.01. The solid loading in the slurry was 1.1 wt%. The precipitate was then isolated by filtration and washed with DI water until the filtrate conductivity was less than 350 microsiemens / cm (mS / cm). The SEM of the resulting mixed metal hydroxide was Figure 1 The XRD pattern of the product is shown in Figure 7 middle.

[0067] Example 2

[0068] 0.6m mixed metal sulfate solution (Ni / Co=90 / 10) and alkaline solution (i.e., 0.6mNH4OH(aq) and 0.2m NaOH solution) were prepared with DI water. The mixed metal solution and alkaline solution were preheated to 40°C. Equal amounts of the mixed metal solution and alkaline solution (i.e., 100mL each) were premixed in a 1L reaction vessel and maintained at 40°C. The mixed metal solution and alkaline solution were added to the reactor together at a rate of 1mL / min and continued to mix for 5 hours. The pH of the solution was 7.41. The solid loading in the slurry was 1.6wt%. The precipitate was then separated by filtration and washed with DI water until the filtrate conductivity was less than 350μS / cm. The SEM of the product is shown in Figure 2 The XRD of the product is shown in Figure 7 middle.

[0069] Example 3

[0070] A 0.9 m mixed metal sulfate solution (Ni / Co=90 / 10) and two separate alkaline solutions (i.e., 0.9 m NH4OH (aq) and 0.96 m NaOH solution) were prepared with DI water. The mixed metal solution and the two alkaline solutions were preheated to 40°C. Equal amounts of the mixed metal solution and the alkaline solution (i.e., 70 mL each) were mixed in a 1 L reaction vessel and maintained at 40°C. All solutions (i.e., the mixed metal solution and the two alkaline solutions) were added to the reactor together at a rate of 0.7 mL / min and mixed for 5 hours. The pH of the solution was 8.55. The solid loading in the slurry was 2.5 wt%. The precipitate was then separated by filtration and washed with DI water until the filtrate conductivity was less than 350 μS / cm. The SEM of the product is shown in Figure 3 The XRD of the product is shown in Figure 7 middle.

[0071] Example 4

[0072] A 0.9 m mixed metal sulfate solution (Ni / Co=90 / 10) and two separate alkaline solutions (i.e., 0.9 m NH4OH (aq) and 1.29 m NaOH solution) were prepared with DI water. The mixed metal sulfate solution and the two alkaline solutions were preheated to 40°C. Equal amounts of the mixed metal sulfate solution and the alkaline solution (i.e., 70 mL each) were premixed in a 1 L reaction vessel and the temperature was maintained at 40°C. The mixed metal sulfate solution and the two alkaline solutions were added to the reactor together at a rate of 0.7 mL / min, and then mixed for 5 hours. The pH of the solution was 9.54. The solid loading in the slurry was 2.6 wt % based on the total weight of the slurry. The precipitate was then separated by filtration and washed with DI water until the filtrate conductivity was less than 350 μS / cm. The SEM of the product is shown in Figure 4The XRD of the product is shown in Figure 7 middle.

[0073] Example 5

[0074] Prepare 2.1m mixed metal sulfate solution (Ni / Co / Mn=1.89m / 0.105m / 0.105m) and two separate alkaline solutions (i.e., 15m NH4OH(aq) and 8.33m NaOH solution) with DI water. When preparing the mixed metal sulfate solution and the NaOH solution, use N2 purge continuously to displace any dissolved oxygen in the solution to avoid Mn oxidation in the subsequent coprecipitation. For the NH4OH(aq) solution, purge an appropriate amount of water with N2 and then stop the N2 purge, followed by adding the desired amount of concentrated NH4OH(aq). The mixed metal solution and the two alkaline solutions are preheated to 40°C. The mixed metal solution and the alkaline solution are then premixed in a 1L reaction vessel at a ratio of 14:2:5 (e.g., 140, 20, and 50 mL, respectively, for mixed metals, NH4OH(aq), and NaOH) and maintained at 40°C. The mixed metal sulfate solution and two alkaline solutions were added to the reactor at flow rates of 1.4, 0.2 and 0.5 mL, respectively, and mixing continued for 5 hours. The solution was continuously purged with N2 and covered with N2 to prevent oxidation of the transition metals.

[0075] The pH of the solution was 8.92. The solid loading in the slurry was 8.9 wt % based on the total weight of the slurry. The precipitate was then isolated by filtration and washed with DI water until the filtrate conductivity was less than 350 μS / cm.

[0076] The SEM of the product is shown in Figure 4 The XRD of the product is shown in Figure 8 middle.

[0077] Example 6

[0078] The product of Example 5 was mixed with 15 μm lithium hydroxide monohydrate at a molar ratio of Li / Me=1.08, wherein Me is a combination of metals Ni, Co and Mn, and then calcined at 900° C. for 10 hours under an oxygen atmosphere. Fig. 9 The XRD pattern is shown and indicates that the product has a highly ordered The layered cathode active material (CAM) has a low Li / Ni cation disorder of 2.17 mol% and a trace amount of lithium sulfate. The results of the particle size distribution analysis are shown in Fig.11 The product had a D50 of 2.01 micrometers (μm) and a D90 of 5.03 μm.

[0079] Example 7

[0080] The product of Example 6 was further subjected to washing to remove residual Li compounds. Three grams (g) of CAM of Example 6 were rinsed with 60 g of cold DI water (T<10° C.) for 10 minutes. The CAM was filtered and rinsed with another 60 g of cold DI water. The rinse water was analyzed for residual Li by titration. Based on the total weight of CAM before washing, the residual LiOH and Li2CO3 were 0.09 wt% and 0.04 wt%, respectively. The wet cake was further dried and analyzed by XRD to ensure structural integrity. Fig.10 As shown, the XRD pattern after the washing procedure is essentially the same as Example 6, but without the small peak associated with trace amounts of lithium sulfate.

[0081] Comparative Example 2

[0082] The product of Comparative Example 1 was calcined as described in Example 6. The particle size distribution is shown in Fig.12 D50 is 12.43 mm; D90 is 20.47 mm. The XRD of the product is shown in Fig.13 middle.

[0083] Example 8: Electrochemical evaluation of the product of Example 7

[0084] The cathode active material from Example 7 was mixed with conductive carbon (LITX from Cabot Corporation) using N-methyl-2-pyrrolidone (NMP) as solvent. TM HP), and polyvinylidene fluoride (PVDF) adhesives (Kynar from Arkema TM 500) were mixed in a weight ratio of 94:3:3 to prepare a slurry. TM The PVDF binder and conductive carbon were mixed in a mixer. First, the PVDF binder and conductive carbon were mixed with NMP to provide a uniform mixture. Then, the cathode active material and additional NMP were added and mixed until the desired viscosity (2000 to 5000 centipoise (cP)) was obtained. The final solid content was about 65wt% based on the total weight of the mixture to achieve a slurry with a honey-like consistency. Al foil was used as the current collector and a pull-down rod coater was used as the coating equipment for the slurry. The coated slurry was quickly dried at 60°C for 5 minutes, and then quickly dried at 120°C for 5 minutes, and then vacuum dried at 110°C overnight. The mass loading target of the cathode active material is about 20mg / cm 2 Calendering was performed to achieve a final coating thickness of 30% of the target compacted porosity, resulting in a cathode with a coating thickness of 110 microns.

[0085] Electrochemical evaluations were performed using 2032-type button cells using the cathode, Li metal as anode, and an electrolyte of 1.2M LiPF6 in EC:EMC (3:7) with 2wt% VC based on the total weight of LiPF6, EC, and EMC. After assembly, each cell was given a 6-hour rest period before forming cycles. The forming cycle consisted of C / 10 charging to 4.3V with a constant voltage (CV) maintained at 4.3V until the current density dropped to C / 20, followed by a C / 10 discharge to 2.8V with a 10-minute rest period. After 3 forming cycles, the cell was placed in a C / 3 charge and discharge cycle for 100 cycles. The charge and discharge rates were determined based on the weight of the cathode active material and assuming 230mAh / g.

[0086] The present disclosure further encompasses the following aspects.

[0087] Aspect 1. A method for preparing a single crystal cathode active material, the method comprising: providing a metal salt solution containing nickel, cobalt, manganese, aluminum, or a combination thereof; combining the metal salt solution with an alkaline solution, wherein the combination of the metal salt solution and the alkaline solution is maintained at a pH of not more than 10 to form a metal hydroxide precursor; adding a lithium compound to the metal hydroxide precursor to form a metal hydroxide precursor mixture; and heat treating the mixture to form a single crystal cathode active material.

[0088] Aspect 2. The method according to aspect 1, wherein the pH is at least 7, preferably at least 8.

[0089] Aspect 3. The method according to aspect 1 or 2, wherein the metal salt solution is a metal sulfate solution in water, preferably an aqueous solution comprising NiSO4·-6H2O, MnSO4·H2O and CoSO4·7H2O.

[0090] Aspect 4. A method according to any one of the preceding aspects, wherein the alkaline solution comprises an alkali metal hydroxide, ammonium hydroxide or a combination thereof, preferably sodium hydroxide and ammonia, more preferably wherein the sodium hydroxide and ammonia are present in a ratio of 2:1 to 1:2, preferably 1.5:1 to 1:1.5, more preferably 1.2:1 to 1:1.

[0091] Aspect 5. The method according to any one of the preceding aspects, wherein the metal hydroxide precursor mixture is semi-crystalline and comprises a β phase (B) and an intermediate phase (I).

[0092] Aspect 6. The method according to aspect 5, wherein the β phase has a formula M(OH)2, wherein M comprises Ni, Mn, Co, Al, or a combination thereof, and the β phase is characterized in that when Cu K α The radiation, when analyzed by X-ray diffraction, has a peak at 17 to 23 degrees 2θ.

[0093] Aspect 7. The method according to aspect 5 or 6, wherein the intermediate phase has the formula M(OH)2·yZ, where M includes Ni, Mn, Co, Al, or a combination thereof, and where 0 < y < 0.75 and Z represents H2O, a solvent, an anion, or a combination thereof, where the solvent is preferably ROH or RCOOH, where R is an alkyl group having 1 to 3 carbon atoms, or Z is preferably OH - , SO4 2- , NO3 - , CO3 2- , F - , Cl - , or a combination thereof, more preferably H2O or SO4 2- , more preferably H2O.

[0094] Aspect 8. The method according to any one of the preceding aspects, wherein nickel, cobalt, manganese, aluminum, or a combination thereof is included in a molar ratio of Ni:Co:Mn greater than 0 to 1: greater than 0 to 1: greater than 0 to 1, preferably 1:0.125:0.125, and most preferably 1:0.18:0.18.

[0095] Aspect 9. The method according to any one of the preceding aspects, wherein the metal hydroxide precursor comprises a residual S content of at least 0.1 wt% to less than 3 wt%, preferably less than 2.5 wt%, and more preferably less than 2 wt%, each based on the total weight of the metal hydroxide precursor.

[0096] Aspect 10. The method according to any one of the preceding aspects, wherein the lithium compound includes lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or a combination thereof.

[0097] Aspect 11. The method according to any one of the preceding aspects, wherein the heat treatment includes heat treatment at a temperature of 600 to 1100 °C, preferably 800 to 1000 °C, and more preferably 850 to 950 °C for 2 to 24 hours.

[0098] Aspect 12. The method according to any one of the preceding aspects, wherein there is only one heat treatment step.

[0099] Aspect 13. The method according to any one of the preceding aspects, wherein the molar ratio of the lithium compound to the metal hydroxide precursor is 1 to 1.2, preferably 1.02 to 1.15, and more preferably 1.05 to 1.10.

[0100] Aspect 14. The method according to any one of the preceding aspects, wherein the cathode active material has the formula Li x MO2, where M is Ni, Co, Mn, Al, or a combination thereof, and 0 < x ≤ 1.2.

[0101] Aspect 15. The method according to aspect 14, wherein the cathode active material has the formula Li x Ni y Co z Mn v O2, where 0 < x ≤ 1.2 and 0.8 ≤ (y + z + v) ≤ 1.1. Preferably, y is from 0.1 to 1, z is from 0.01 to 0.1, and v is from 0.01 to 0.1. More preferably, it has the formula LiNi 0.88 Co 0.06 Mn 0.06 O2.

[0102] Aspect 16. The method according to any one of the preceding aspects, wherein the cathode active material formed during the heat treatment comprises monodisperse single crystals having a unimodal particle size distribution.

[0103] Aspect 17. The method according to any one of the preceding aspects, wherein the cathode active material comprises single crystals having a D50 particle size greater than 100 nm and less than 10 μm, preferably 1 to 5 μm, more preferably 1 to 3 μm, as measured according to ASTM C115.

[0104] Aspect 18. The method according to any one of the preceding aspects, wherein the cathode active material comprises single crystals having a D90 particle size greater than 1 μm and less than 20 μm, preferably 3 to 10 μm, more preferably 5 to 8 μm, as measured according to ASTM C115.

[0105] Aspect 19. The method according to any one of the preceding aspects, further comprising washing the cathode active material after the heat treatment.

[0106] Aspect 20. The method according to any one of the preceding aspects, wherein, based on the total weight of the cathode active material, the cathode active material on the surface thereof comprises less than 10, preferably less than 7 wt% of residual lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium sulfate, or a combination thereof.

[0107] Aspect 21. The method according to any one of the preceding aspects, wherein the cathode active material is characterized in that for a half-cell at a discharge rate of C / 3 after 100 cycles, the average discharge capacity is greater than 200 mAh / g.

[0108] Aspect 22. The method according to any one of the preceding aspects, wherein the metal salt solution comprises metals obtained from recycled raw materials, preferably metals obtained from post-industrial recycled raw materials, post-consumer recycled raw materials, or a combination thereof.

[0109] Aspect 23. The method according to any one of the preceding aspects, wherein the mixture subjected to the heat treatment step comprises 0.1 to 5 wt% of lithium carbonate.

[0110] Aspect 24. A method for preparing a monodisperse single crystal cathode active material, the method comprising: providing a metal hydroxide precursor comprising nickel, cobalt, manganese, aluminum, or a combination thereof, wherein the metal hydroxide precursor is characterized as being semi-crystalline and comprising a β phase and an intermediate phase, wherein the β phase is characterized in that when Cu K α The radiation has a peak at 17 to 23 degrees 2θ when analyzed by X-ray diffraction,

[0111] The mesophase is characterized in that H2O, ROH, RCOOH, anions, or combinations thereof are incorporated into the structure of the mesophase, wherein R is an alkyl group of 1 to 3 carbon atoms; a lithium compound is added to a metal hydroxide precursor to form a mixture, and the mixture is heated in a one-step calcination to form a monodisperse single crystalline cathode active material having a monomodal particle size distribution and a D50 particle size distribution of 100 nm to 5 μm or a D90 particle size distribution of 1 to 10 μm.

[0112] Aspect 25. The method according to aspect 24, wherein the anion comprises OH - 、SO4 2- 、NO3 - 、CO3 2- 、F - , Cl - , or a combination thereof.

[0113] Aspect 26. The method according to Aspect 24, wherein water, sulfate ions, or both are incorporated into the structure of the mesophase.

[0114] Aspect 27. The method according to any one of aspects 24-26, wherein the β phase has the formula M(OH)2, wherein M is Ni, Co, Mn, Al, or a combination thereof.

[0115] Aspect 28. A method according to any one of Aspects 24-27, wherein nickel, cobalt, manganese, aluminum, or a combination thereof comprises nickel, cobalt and manganese, and the molar ratio of Ni:Co:Mn is greater than 0 to 1: greater than 0 to 1: greater than 0 to 1, preferably 1:0.125:0.125, and most preferably 1:0.18:0.18 (90 / 5 / 5).

[0116] Aspect 29. The method according to any one of aspects 24 to 28, wherein the lithium compound comprises lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or a combination thereof.

[0117] Aspect 30. The method according to any one of aspects 24 to 29, wherein the heat treatment comprises heating at a temperature of 600 to 1100° C., preferably 800 to 1000° C. or more preferably 850 to 950° C. for 2 to 24 hours.

[0118] Aspect 31. The method according to any one of aspects 24 - 30, wherein the molar ratio of the lithium compound to the metal hydroxide precursor is from 1 to 1.2, preferably from 1.02 to 1.15, more preferably from 1.05 to 1.10.

[0119] Aspect 32. The method according to any one of aspects 24 - 31, wherein the cathode active material has the formula Li x MO2, where M is Ni, Co, Mn, Al, or a combination thereof, and 0 < x ≤ 1.2.

[0120] Aspect 33. The method according to aspect 32, wherein the cathode active material has the formula Li x Ni y Co z Mn v O2, where 0 < x ≤ 1.2 and 0.8 ≤ (y + z + v) ≤ 1.1. Preferably, y is from 0.1 to 1, z is from 0.01 to 0.1, and v is from 0.01 to 0.1. More preferably, it has the formula LiNi 0.88 Co 0.06 Mn 0.06 O2.

[0121] Aspect 34. The method according to any one of aspects 24 - 33, further comprising washing the cathode active material after the heat treatment.

[0122] Aspect 35. The method according to any one of aspects 24 - 34, wherein, based on the total weight of the cathode active material, the cathode active material on the surface of the cathode active material contains less than 10 wt% of residual lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium sulfate, or a combination thereof.

[0123] Aspect 36. The method according to any one of aspects 24 - 35, wherein the cathode active material is characterized in that for a half - cell at a discharge rate of C / 3 after 100 cycles, the average discharge capacity is greater than 200 mAh / g.

[0124] Aspect 37. The method according to any one of aspects 24 - 36, wherein the mixture subjected to the heat treatment contains 0.1 to 5 wt% of lithium carbonate.

[0125] Aspect 38. A metal hydroxide composition comprising: a metal hydroxide comprising nickel, cobalt, manganese, aluminum, or a combination thereof, wherein the metal hydroxide is characterized as semi - crystalline and comprises a β - phase and an intermediate phase. The β - phase is characterized in that when using Cu K αWhen analyzed by X-ray diffraction, the radiation has a peak at 17 to 23 degrees 2θ and has the formula M(OH)2, where M is Ni, Co, Mn, Al, or a combination thereof.

[0126] The mesophase is characterized by binding H2O, ROH, RCOOH, anions, or a combination thereof to the structure of the mesophase, where R is an alkyl group having 1 to 3 carbon atoms.

[0127] Aspect 39. The metal hydroxide composition according to aspect 38, wherein water, sulfate ions, or both are bound to the structure of the mesophase.

[0128] Aspect 40. A single-crystal cathode active material having the formula Li x MO2, where M is Ni, Co, Mn, Al, or a combination thereof, and 0 < x ≤ 1.2, characterized in that the monodisperse single crystal with a single-peak particle size distribution has a D50 particle size distribution of 100 nm to 5 μm or a D90 particle size of 1 to 10 μm, and Li2SO4 is present.

[0129] Aspect 41. The single-crystal active material according to aspect 40, wherein when analyzed by X-ray diffraction using Cu K α radiation, the presence of Li2SO4 is determined by a peak at 22 to 29 degrees 2θ.

[0130] Aspect 42: The single-crystal active material of aspect 40 or 42 prepared by the method of any one of aspects 1 - 37.

[0131] Aspect 43: The metal hydroxide composition of aspect 38 or 39 prepared by a method comprising: providing a metal salt solution comprising nickel, cobalt, manganese, aluminum, or a combination thereof; combining the metal salt solution with an alkaline solution, wherein the combination of the metal salt solution and the alkaline solution is maintained at a pH not greater than 10 and preferably at least 7, more preferably at least 8, to form a metal hydroxide precursor.

[0132] All ranges disclosed herein include endpoints, and the endpoints can be combined independently of each other (e.g., a range of "up to 25 wt.%, or more specifically, 5 wt.% to 20 wt.%" includes the endpoints and all intermediate values of the range of "5 wt.% to 25 wt.%", etc.). In addition, the upper and lower limits can be combined to form a range (e.g., "at least 1 or at least 2 weight percentages" and "up to 10 or 5 weight percentages" can be combined as the range "1 to 10 weight percentages", or "1 to 5 weight percentages" or "2 to 10 weight percentages" or "2 to 5 weight percentages"). Unless otherwise specifically stated, "or" means "and / or".

[0133] Alternatively, the present disclosure may include, consist of, or consist essentially of any suitable component disclosed herein. The present disclosure may additionally or alternatively be formulated so as to be free of or substantially free of any component, material, ingredient, adjuvant or substance used in prior art compositions or not necessary to achieve the function and / or purpose of the present disclosure.

[0134] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in the present application contradicts or conflicts with a term in the incorporated reference, the term from the present application takes precedence over the conflicting term from the incorporated reference.

[0135] Unless specified to the contrary herein, all test standards are the most recent standards in effect as of the filing date of this application, or, if priority is claimed, as of the filing date of the earliest priority application in which the test standards appear.

Claims

1. A method for preparing a single crystal cathode active material, the method comprising: providing a metal salt solution comprising nickel, cobalt, manganese, aluminum, or a combination thereof; combining the metal salt solution with an alkaline solution, wherein the combination of the metal salt solution and the alkaline solution is maintained at a pH of no greater than 10 to form a metal hydroxide precursor; adding a lithium compound to the metal hydroxide precursor to form a metal hydroxide precursor mixture; and The metal hydroxide precursor mixture is heat treated to form the single crystalline cathode active material.

2. The method according to claim 1, wherein: The pH is at least 7, preferably at least 8.

3. The method according to claim 1, wherein: The metal salt solution is a metal sulfate solution in water, preferably an aqueous solution comprising NiSO4.6H2O, MnSO4.H2O and CoSO4.7H2O; and The alkaline solution comprises an alkali metal hydroxide, ammonium hydroxide or a combination thereof, preferably sodium hydroxide and ammonia, more preferably, wherein the sodium hydroxide and ammonia are present in a ratio of 2:1 to 1:2, preferably 1.5:1 to 1:1.5, more preferably 1.2:1 to 1:

1.

4. The method according to claim 1, wherein: The metal hydroxide precursor mixture is semi-crystalline and comprises a beta phase (B) and an intermediate phase (I).

5. The method according to claim 4, wherein: The β phase has a formula M(OH)2, wherein M comprises Ni, Mn, Co, Al, or a combination thereof, and is characterized in that when Cu K α The radiation, when analyzed by X-ray diffraction, has a peak at 17 to 23 degrees 2θ; and The intermediate phase has the formula M(OH)2·yZ, where M includes Ni, Mn, Co, Al, or a combination thereof, and where 0 < y < 0.75 and Z represents H2O, a solvent, an anion, or a combination thereof, where the solvent is preferably ROH or RCOOH, where R is an alkyl group having 1 to 3 carbon atoms, or Z is preferably OH - , SO4 2- , NO3 - , CO3 2- , F - , Cl - , or a combination thereof, more preferably H2O or SO4 2- , more preferably H2O.

6. The method according to claim 1, wherein: The nickel, cobalt, manganese, aluminum, or a combination thereof comprises nickel, cobalt and manganese in a molar ratio of Ni:Co:Mn of greater than 0 to 1: greater than 0 to 1: greater than 0 to 1, preferably 1:0.125:0.125, most preferably 1:0.18:0.

18.

7. The method according to claim 1, wherein: The metal hydroxide precursor comprises a residual S content of at least 0.1 wt % to less than 3 wt %, preferably 0.1 to less than 2.5 wt %, more preferably 0.1 to less than 2 wt %, each based on the total weight of the metal hydroxide precursor.

8. The method according to claim 1, wherein: The lithium compound includes lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or a combination thereof.

9. The method according to claim 1, wherein: The heat treatment includes heat treatment at a temperature of 600 to 1100° C., preferably 800 to 1000° C., and more preferably 850 to 950° C. for 2 to 24 hours.

10. The method according to claim 1, wherein: There is only one heat treatment step.

11. The method according to claim 1, wherein: The molar ratio of the lithium compound to the metal hydroxide precursor is 1 to 1.2, preferably 1.02 to 1.15, more preferably 1.05 to 1.

10.

12. The method according to claim 1, wherein: The cathode active material has the formula Li x MO2, wherein M is Ni, Co, Mn, Al, or a combination thereof, and 0 <x≤1.2。 13. The method according to claim 12, wherein: The cathode active material has the formula Li x Ni y Co z Mn v O2, where 0 < x ≤ 1.2 and 0.8 ≤ (y + z + v) ≤ 1.1, preferably, where y is from 0.1 to 1, z is from 0.01 to 0.1, and v is from 0.01 to 0.1, and more preferably has the formula LiNi 0.88 Co 0.06 Mn 0.06 O2.

14. The method according to claim 1, wherein: The cathode active material formed during the heat treatment comprises monodisperse single crystals having a monomodal particle size distribution.

15. The method according to claim 1, wherein: The cathode active material comprises a single crystal having: A D50 particle size greater than 100 nm and less than 10 μm, preferably 1 to 5 μm, more preferably 1 to 3 μm, as determined according to ASTM C115; and D90 particle size measured according to ASTM C115 of greater than 1 μm and less than 20 μm, preferably 3 to 10 μm, more preferably 5 to 8 μm.

16. The method according to claim 1, wherein: The cathode active material comprises less than 10 wt %, preferably less than 7 wt % of residual lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium sulfate, or a combination thereof on the surface of the cathode active material based on the total weight of the cathode active material.

17. The method according to claim 1, wherein: The cathode active material is characterized in that for a half-cell at a discharge rate of C / 3 after 100 cycles, the average discharge capacity is greater than 200 mAh / g.

18. The method according to claim 1, wherein: The metal salt solution contains metals obtained from recycled raw materials, preferably metals obtained from post-industrial recycled raw materials, post-consumer recycled raw materials, or a combination thereof.

19. The method according to claim 1, wherein: The mixture subjected to the heat treatment step contains 0.1 to 5 wt% of lithium carbonate.

20. A method for preparing a monodisperse single-crystalline cathode active material, the method comprising: providing a metal hydroxide precursor comprising nickel, cobalt, manganese, aluminum, or a combination thereof, wherein the metal hydroxide precursor is characterized as semi-crystalline and comprises: β phase, characterized by the fact that when Cu K α The radiation, when analyzed by X-ray diffraction, has a peak at 17 to 23 degrees 2θ, and The intermediate phase is characterized in that H2O, ROH, RCOOH, anions, or a combination thereof are incorporated into the structure of the intermediate phase, wherein the anions include OH - 、SO4 2- 、NO3 - 、CO3 2- 、F - , Cl - , or a combination thereof, preferably, wherein water, sulfate ions, or both are incorporated into the structure of the mesophase, wherein R is an alkyl group of 1 to 3 carbon atoms; adding a lithium compound to the metal hydroxide precursor to form a mixture; and heating the mixture in a one-step calcination to form the monodisperse single-crystalline cathode active material, the monodisperse single-crystalline cathode active material having a unimodal particle size distribution and a D50 particle size distribution of 100 nm to 5 μm, a D90 particle size distribution of 1 to 10 μm, or both.

21. The method according to claim 20, wherein: The β-phase has the formula M(OH)2, wherein M is Ni, Co, Mn, Al, or a combination thereof.

22. The method according to claim 20, wherein: The nickel, cobalt, manganese, aluminum, or combination thereof comprises nickel, cobalt, and manganese, and the molar ratio of Ni:Co:Mn is greater than 0 to 1: greater than 0 to 1: greater than 0 to 1, preferably 1:0.125:0.125, and most preferably 1:0.18:0.

18.

23. The method according to claim 20, wherein: The lithium compound includes lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, or a combination thereof.

24. The method according to claim 20, wherein: The heat treatment includes heating at a temperature of 600 to 1100 °C, preferably 800 to 1000 °C, or more preferably 850 to 950 °C for 2 to 24 hours.

25. The method according to claim 20, wherein: The molar ratio of the lithium compound to the metal hydroxide precursor is 1 to 1.2, preferably 1.02 to 1.15, and more preferably 1.05 to 1.

10.

26. The method of claim 20, wherein: The cathode active material has the formula Li x MO2, where M is Ni, Co, Mn, Al, or a combination thereof, and 0 < x ≤ 1.

2. Preferably, the cathode active material has the formula Li x Ni y Co z Mn v O2, where 0 < x ≤ 1.2 and 0.8 ≤ (y + z + v) ≤ 1.

1. Preferably, y is from 0.1 to 1, z is from 0.01 to 0.1, and v is from 0.01 to 0.

1. More preferably, it has the formula LiNi 0.88 Co 0.06 Mn 0.06 O2.

27. The method according to claim 20, wherein: Based on the total weight of the cathode active material, on the surface of the cathode active material, the cathode active material contains less than 10 wt% of residual lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium sulfate, or a combination thereof.

28. The method of claim 20, wherein: The cathode active material is characterized in that for a half-cell at a discharge rate of C / 3 after 100 cycles, the average discharge capacity is greater than 200 mAh / g.

29. The method according to claim 20, wherein: The mixture subjected to the heat treatment contains 0.1 to 5 wt% of lithium carbonate.

30. A metal hydroxide composition, comprising: A metal hydroxide comprising nickel, cobalt, manganese, aluminum, or a combination thereof, wherein: The metal hydroxide is semi-crystalline and comprises: β phase, characterized by the fact that when Cu K α radiation, when analyzed by X-ray diffraction, with a peak at 17 to 23 degrees 2θ; and having the formula M(OH)2, wherein M is Ni, Co, Mn, Al, or a combination thereof, and an intermediate phase, which is characterized in that H2O, ROH, RCOOH, anions, or a combination thereof are bound to the structure of the intermediate phase, wherein R is an alkyl group having 1 to 3 carbon atoms, and preferably, wherein water, sulfate ions, or both are bound to the structure of the intermediate phase.

31. A single crystal cathode active material having the formula Li x MO2, where M is Ni, Co, Mn, Al, or a combination thereof, and 0 < x ≤ 1.2, which is characterized in that the monodisperse single-crystalline having a unimodal particle size distribution has a D50 particle size distribution of 100 nm to 5 μm, a D90 particle size of 1 to 10 μm, or both, and Li2SO4 is present.

Citation Information

Patent Citations

  • Method for synthesizing nickel-cobalt-aluminum electrodes

    WO2020082019A1

  • Cost effective synthesis of oxide materials for lithium ion batteries

    WO2022026014A2